JSMeter: Characterizing Real-World Behavior of JavaScript Programs - Ratanaworabhan, Paruj; Livshits, Ben; Simmons, David; Zorn, Ben and (2009)
JavaScript is widely used in web-based applications and is increasing popular with developers. So-called ”browser wars” in recent years have focused on JavaScript performance, specifically claiming comparative results based on benchmark suites such as SunSpider and V8. In this paper we evaluate the behavior of JavaScript web applications from commercial websites and compare this behavior with the benchmarks. We measure three specific areas of JavaScript runtime behavior: 1) functions and code; 2) heap-allocated objects and data; 3) events and handlers. We find that the benchmarks are not representative of many real websites and that conclusions reached from measuring the benchmarks may be misleading. Specific examples of such misleading conclusions include the following: that web applications have many loops, that non-string objects in web applications are extremely short-lived, and that web applications handle few events. We hope our results will convince the JavaScript community to develop and adopt benchmarks that are more representative of real web applications.